Regulation of the Mitotic Exit Protein Kinases Cdc15 and Dbf2 - Visintin, Rosella (The American Society for Cell Biology, 2001)
In budding yeast, the release of the protein phosphatase Cdc14 from its inhibitor Cfi1/Net1 in the nucleolus during anaphase triggers the inactivation of Clb CDKs that leads to exit from mitosis. The mitotic exit pathway controls the association between Cdc14 and Cfi1/Net1. It is comprised of the RAS-like GTP binding protein Tem1, the exchange factor Lte1, the GTPase activating protein complex Bub2-Bfa1/Byr4, and several protein kinases including Cdc15 and Dbf2. Here we investigate the regulation of the protein kinases Dbf2 and Cdc15. We find that Cdc15 is recruited to both spindle pole bodies (SPBs) during anaphase. This recruitment depends on TEM1 but not DBF2 or CDC14 and is inhibited by BUB2. Dbf2 also localizes to SPBs during anaphase, which coincides with activation of Dbf2 kinase activity. Both events depend on the mitotic exit pathway components TEM1 and CDC15. In cells lacking BUB2, Dbf2 localized to SPBs in cell cycle stages other than anaphase and telophase and Dbf2 kinase was prematurely active during metaphase. Our results suggest an order of function of mitotic exit pathway components with respect to SPB localization of Cdc15 and Dbf2 and activation of Dbf2 kinase. BUB2 negatively regulates all 3 events. Loading of Cdc15 on SPBs depends on TEM1, whereas loading of Dbf2 on SPBs and activation of Dbf2 kinase depend on TEM1 and CDC15.